Tinjauan Kelaiklautan Kapal Tradisional Yang Beroperasi Di Wilayah Jakarta • Kepulauan Seribu - Malisan, Johny (Warta Penelitian Perhubungan, 2012)
ABSmACTNumber of wooden-ships (people called them as kapal ojek) operated in 2011 are 34 vessels or equal to 1,199 gross tonnage and total capacity of 1,833 passengers. Since many accidents of ships occurs and to be public concern, the author is interested to make research in order to evaluate sea worthiness of their stability and users' opinion. 17tere are 5 aspect of opinions to be collected among others safety equipments, timeliness and ships availability, security and comfort, crews competencies, and tariff. Users' opinion is analyzed by using the Importance performance Index and Customer Satisfaction Index The results shows that many variables are still needed to improve tlmt could enhance the service performance of those ships. 17teir stabilities are relatively in good condition, but should always consider to loading and weather conditions because the ships are made of woods and low of freeboards.Keywords : ship safety, ship seaworthiness, ship stability